2013
DOI: 10.2478/v10247-012-0078-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil quality associated with tillage system applied

Abstract: The aim of this research was to evaluate changes in soil quality associated with the tillage system applied with chosen parameters of soil biological properties. The long-term field experiments were located at a private farm in Rogów (Zamooeć region, E Poland) on a silt soil and at the Experimental Station in Laskowice (Wrocław region, S-W Poland) on a sandy loam soil. Soil samples were collected from 0-15 and 15-30 cm layers. Winter wheat was grown under traditional, reduced and no-tillage systems. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 23 publications
(33 reference statements)
2
40
0
1
Order By: Relevance
“…Negative impacts of CT on MBC and MBN contents were also confirmed by numerous studies, e.g. Spedding et al (2004) and Gajda et al (2013).…”
Section: Resultssupporting
confidence: 48%
“…Negative impacts of CT on MBC and MBN contents were also confirmed by numerous studies, e.g. Spedding et al (2004) and Gajda et al (2013).…”
Section: Resultssupporting
confidence: 48%
“…In intensively cultivated rows, the values of CSC in WSA mi were higher (by 15%) in comparison to those from the grassy strips in-between the vineyard rows. Tisdall and Oades (1980) reported that higher carbon content is in the macro-rather than in the micro-aggregates and also its content is influenced by the land use or soil management practices used (Balashov & Buchkina 2011;Šimanský 2012;Gaida et al 2013). For example, Tisdall and Oades (1980) also reported that due to a greater biomass (plant roots, microscopic fungal hyphae), in soils from meadows or native grasslands the carbon content in macro-aggregates is higher.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, the highest content of C org and C L in WSA was determined in the grassy strips in-between the vineyard rows, rather than in the intensively cultivated rows themselves. This can be seen as a result of tillage and the intensive cultivation of soil (Beare et al 1994;Šimanský et al 2008;Balashov & Buchkina 2011;Gaida et al 2013). Carbon sequestration capacity in water-stable aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that approach, CO 2 production is one of the biological indicators of soil conditions because organic matter hosts microbial activity. Aerobic and anaerobic decomposers use organic matter as a source of nutrients and energy for their growth and functioning (Gajda and Przew³oka, 2012., Gajda et al, 2013;Šantrùèková et al, 2010).…”
Section: Introductionmentioning
confidence: 99%